Chemical and microbiological quality of fermented sausages made from camel meat - Kök, Filiz; Öksüztepe, Gülsüm; İlhak, O. İrfan; Patır, Bahri (My University, 2006)
Chemical and microbiological quality parameters of 100 fermented sausage samples made from camel meat were investigated in the Aydin region. The results showed that the mean pH value noted in the sausages was 6.00 ± 0.25. Additionally, the mean moisture, aw, fat, ash and salt contents of the sausages were 37.69 ± 4.32%, 0.852 ± 0.02, 33.6 ± 4.35%, 3.99 ± 0.47% and 3.28 ± 0.41%, respectively. The mean TVC of the samples was 4.85 ± 0.47 log cfu g-1, whereas the mean numbers of staphylococci/micrococci, yeast and mould, lactic streptococci, lactobacilli, and coliforms were 4.78 ± 0.40 log cfu g-1, 2.88 ± 1.06 log cfu g-1, 4.07 ± 0.46 log cfu g-1 , 2.82 ± 0.98 log cfu g-1, and <1.0 log cfu g-1, respectively. In conclusion, the study found that there were variations in the chemical and microbiological parameters in the investigated sausages. The variations in the microbiological load and chemical results of sausages produced from camel meat may be due to insufficient standardization procedures applied during processing, no starter culture usage and the lack of hygienic practices. Camel meat sausages are a specialty of the Aydin region and thus their production should be standardized. Additionally, providing good hygienic practices during the production process will protect public health and provide healthy sausages for consumers.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Makale - Yabancı Dilde Makale
Keywords: Sausage Camel meat Microbiology